EVALUATING AVERAGE EARNINGS MANAGEMENT OF CORPORATES BY THE MANAGERS BEFORE AND AFTER AUDIT COMMITTEE FORMATION - Soheil Harivandi; Hossien Khanjani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The present research aims to evaluate the average earnings management of the corporates listed on the Tehran stock exchange. The statistic population included the corporates listed on the Tehran stock exchange from 2008 to 2013. Eighty-seven corporates were selected as the sample volume by screening method and after omitting the wild observations. In this study. The audit committee expertise was regarded as the independent variable to study its influence on the quality of earnings forecasts and corporates earnings management. The mixed models and the panel data with fixed effects were applied in this research. The results obtained from the corporates data analysis by applying multivariable regression at a %95 confidence level reveal that the average earnings management has been reduced after the audit committee formation.